2014
DOI: 10.1007/s40261-014-0204-3
|View full text |Cite
|
Sign up to set email alerts
|

Ready Conversion of Patients with Well-Controlled, Moderate to Severe, Chronic Malignant Tumor–related Pain on Other Opioids to Tapentadol Extended Release

Abstract: Background and ObjectivesThe effectiveness and tolerability of tapentadol extended release (ER), a centrally acting analgesic with μ-opioid receptor agonist and norepinephrine (noradrenaline) reuptake inhibitor activities, have been demonstrated in patients with chronic pain, including those switching directly from prior opioid therapy. The objective of the current study was to evaluate the effectiveness and safety of conversion to oral tapentadol ER (50–250 mg twice daily) from previous around-the-clock stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…[36][37][38]42,45,56 The concomitant use of WHO step I analgesics and coanalgesics was permitted in the 4 previously described open-label, Phase IIIb studies of tapentadol PR in patients with low back pain with or without a neuropathic pain component 37,45 or with osteoarthritis knee pain. 38 42,85,86 tapentadol PR used concomitantly with morphine IR and oxycodone IR was well tolerated. Although only the concomitant use of morphine IR and oxycodone IR for breakthrough pain has been evaluated, these findings suggest that other IR opioids could be safely used as well.…”
Section: Concomitant Analgesics and Coanalgesicsmentioning
confidence: 93%
“…[36][37][38]42,45,56 The concomitant use of WHO step I analgesics and coanalgesics was permitted in the 4 previously described open-label, Phase IIIb studies of tapentadol PR in patients with low back pain with or without a neuropathic pain component 37,45 or with osteoarthritis knee pain. 38 42,85,86 tapentadol PR used concomitantly with morphine IR and oxycodone IR was well tolerated. Although only the concomitant use of morphine IR and oxycodone IR for breakthrough pain has been evaluated, these findings suggest that other IR opioids could be safely used as well.…”
Section: Concomitant Analgesics and Coanalgesicsmentioning
confidence: 93%
“…Nine studies were found with the aforementioned characteristics (4 randomized clinical trials and five nonrandomized, open‐label trials or clinical practice studies) (see Flow Diagram in Figure , Tables and ). Of the randomized trials, one of them is an open‐label, phase III study, conducted in Japan, to evaluate the efficacy and tolerability of conversion to oral tapentadol ER (50 to 250 mg twice daily) from previous around‐the‐clock strong opioids in subjects with moderate‐to‐severe, chronic cancer pain, with the aim of being able to recommend this change if necessary in clinical practice . A second study was a randomized, placebo‐controlled, double‐blind, phase 3 trial (NCT00472303), conducted in 16 countries, that aimed to evaluate the effectiveness and safety of tapentadol ER compared with placebo and morphine controlled release (CR) for managing moderate‐to‐severe chronic cancer pain .…”
Section: Resultsmentioning
confidence: 99%
“…Together, these studies suggest that dual opioid therapy may have advantages postoperatively in treating pain while reducing side effects [43]. Similarly, Tapentadol is a μ-opioid agonist and norepinephrine reuptake inhibitor that has been found to have fewer gastrointestinal effects, such as constipation and vomiting [44]. Imanaka et al [44] found that Tapentadol was able to induce pain control in 84% of patients with terminal cancer-related pain according to self-reported scores [44].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…Similarly, Tapentadol is a μ-opioid agonist and norepinephrine reuptake inhibitor that has been found to have fewer gastrointestinal effects, such as constipation and vomiting [44]. Imanaka et al [44] found that Tapentadol was able to induce pain control in 84% of patients with terminal cancer-related pain according to self-reported scores [44]. The majority of the un-controlled patients did report some degree of improvement in their condition on Tapentadol [44].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
See 1 more Smart Citation